'Governments base performance-based funding on global rankings indicators': A global trend in higher education finance or a global rankings literature fiction? A comparative analysis of four performance-based funding programs. (July 2020) - Adam, Edmund
Highlights: In Austria, Denmark, and Sweden, the orientation of performance funding on global rankings is weaker than it is assumed. Denmark's new taximeter model increases the share of fixed grants (funding earned regardless of performance). By 2022, Danish universities are projected to lose nearly one-tenth of their current government funding. Finland's 2021–2024 universities funding model de-emphasizes internationalization. Sweden introduces a new component called 'collaboration with the surrounding society' to its research performance funding. Abstract: For nearly two decades now, the rankings literature has continued to suggest that governments are adopting performance-based funding models which prioritize criteria favored by global rankings. This study examines this assertion by analyzing the performance-based funding programs of Austria, Denmark, Finland, and Sweden. The study finds that the orientation of performance-based funding on global rankings is weaker than it is commonly assumed. Except for Finland, the funding volume universities raise from this orientation is not substantial to influence the institutional performance. The study also analyzes the recent structural changes to performance-based funding in each jurisdiction. Policy implications are provided in the conclusion for higher education systems revising their performance-based funding or considering a shift to performance-based accountability.